Potency of Curcuma aeruginosa as A Chemopreventive Candidate Agent on 7,12-Dimethylbenz[a]anthracene (DMBA)-Induced Rat Spleen - Sulfianti, Asri; Hasanah, Nur; Wibowo, Agung Eru; Agustini, Kurnia; Artika, I Made (BRIN, 2019)
Present investigation shows that the extract of C. aeruginosa attenuates DMBA-induced spleen carcinogenesis in Wistar rats. Three-week female Wistar rats were treated with three different C. aeruginosa extract doses (CA1: 40 mg/200 g body weight, BW; CA2: 80 mg/200 g BW; CA3: 160 mg/200 g BW) and were induced with DMBA after one-week administration of these doses. A commercial immunostimulant, and DMBA only were also given to each group as positive and negative control, respectively. The development of tumors was evaluated by investigating the incidence of tumor and tumor multiplicity during the experiment. Spleen mass index and histological parameters such as white pulp, centrum germinativum, and marginalis zone were also examined. Based on our study, the administration of C. aeruginosa extract during and after carcinogen induction gave several impacts on rat carcinogenesis. At the extract dose of 80 mg/200 g BW, tumor incidence of animals were least (P<0.05). However, all doses did not show any effect to the spleen mass index, though the highest dose (160 mg/200 g BW) was found to cause changes in white pulp and marginalis zone boards. This trend indicates that it takes higher dose to cause an immune response effect reaching the organs.